2021
DOI: 10.1038/s41598-021-86018-3
|View full text |Cite
|
Sign up to set email alerts
|

Gnrh2 maintains reproduction in fasting zebrafish through dynamic neuronal projection changes and regulation of gonadotropin synthesis, oogenesis, and reproductive behaviors

Abstract: Restricted food intake, either from lack of food sources or endogenous fasting, during reproductive periods is a widespread phenomenon across the animal kingdom. Considering previous studies show the canonical upstream regulator of reproduction in vertebrates, the hypothalamic Gonadotropin-releasing hormone (Gnrh), is inhibited in some fasting animals, we sought to understand the neuroendocrine control of reproduction in fasted states. Here, we explore the roles of the midbrain neuropeptide, Gnrh2, in inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Finally, pituitary GnRH2 protein content is unchanged in GnRH3 neuron-ablated females, suggesting that GnRH2 did not assume the role of GnRH3 in LH secretion. This result can be supported by the findings that female GnRH2 mutants ( gnrh2 −/− ) and female mutants that lack all GnRHs ( gnrh2 −/− ; gnrh3 −/− ) also maintain normal fertility in zebrafish [ 70 , 71 ]. In WT zebrafish, the number of GnRH2 neurons projecting to the pituitaries and reaching the LH gonadotropes are lower relative to those of GnRH3 neurons [ 70 ].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Finally, pituitary GnRH2 protein content is unchanged in GnRH3 neuron-ablated females, suggesting that GnRH2 did not assume the role of GnRH3 in LH secretion. This result can be supported by the findings that female GnRH2 mutants ( gnrh2 −/− ) and female mutants that lack all GnRHs ( gnrh2 −/− ; gnrh3 −/− ) also maintain normal fertility in zebrafish [ 70 , 71 ]. In WT zebrafish, the number of GnRH2 neurons projecting to the pituitaries and reaching the LH gonadotropes are lower relative to those of GnRH3 neurons [ 70 ].…”
Section: Discussionmentioning
confidence: 71%
“…This result can be supported by the findings that female GnRH2 mutants ( gnrh2 −/− ) and female mutants that lack all GnRHs ( gnrh2 −/− ; gnrh3 −/− ) also maintain normal fertility in zebrafish [ 70 , 71 ]. In WT zebrafish, the number of GnRH2 neurons projecting to the pituitaries and reaching the LH gonadotropes are lower relative to those of GnRH3 neurons [ 70 ]. Therefore, unlike what is reported after fasting [ 70 ], the reduction in the number of GnRH3 neuronal projections to the pituitary may not provoke the plasticity of GnRH2 neurons.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Studies have shown that GnRH depletion is positively correlated with a reduction in GSI and gonadotropin production, further affecting oogenesis, spawning success, fecundity, and male courting behaviour (Marvel et al, 2021). LH and FSH also positively affect the development of zebra sh gonads.…”
Section: Effect Of Cbd On Reproduction-related Gene Expressionmentioning
confidence: 99%
“…In a teleost, the zebrafish, the knockout of either tac3a, tac3b, or both does not disrupt the reproduction (spermatogenesis and folliculogenesis are not impaired) (163). The impact of tac3 gene mutation should be now studied in other teleost species, as knockout studies of reproductive genes such as the different types of gnrh [gnrh3 (164); gnrh2 (165)] and kiss [kiss1, kiss2, kissr1, and kissr2 (166)] system genes all generate zebrafish with normal gametogenesis, suggesting that this species may have a high compensatory mechanism [for reviews (167,168)] and may not reflect the situation observed in all teleosts.…”
Section: Inactivation Of the Tac3 System And Reproductionmentioning
confidence: 99%